Description Of Ferritin Levels In Pregnant Women With Anemia - Farah Irvina; Rahajoe Imam Santosa; Natalia Yuwono (Sean Institute, 2023)
Anemia is a condition in which the body experiences a decrease in the amount of hemoglobin (Hb), leading to insufficient red blood cells to meet physiological needs. Anemia during pregnancy is a condition in which the hemoglobin (Hb) level in the body is less than 11 g/dL. Anemia during pregnancy can be caused by a deficiency of iron, a lack of folic acid, and a deficiency of vitamin B12 in the body. Iron Deficiency Anemia (IDA) is the most common cause of anemia during pregnancy because pregnant women experience an increase in iron demand. Iron Deficiency Anemia (IDA) occurring in pregnant women can have negative impacts on both the mother and the fetus, posing a risk of mortality for both. In the first trimester of pregnancy, the iron required tends to be lower because the amount of iron transferred to the fetus is still low. In the second and third trimesters of pregnancy, the iron in pregnant women increases due to the growth of the fetus and placenta. Ferritin levels examination has proven to have the best sensitivity and specificity compared to other tests for diagnosing IDA. Ferritin is the storage form of iron in the body; Thus, its' levels decrease when the body is experiencing iron deficiency. To understand the description of ferritin levels in pregnant women with anemia. This research is classified as a descriptive observational study using a cross-sectional research design. Ferritin levels in pregnant women with anemia, among the 20 subjects studied, revealed that 13 subjects had normal ferritin levels, accounting for a percentage of 65%, while 7 pregnant women with anemia had low ferritin levels, representing a percentage of 35%. The number of pregnant women with anemia who have normal ferritin levels is higher than those with anemia and low ferritin levels.